Multi-institution Assessment of the Accuracy of Cardiac Computed Tomography in Preparation for Superior Cavopulmonary Connection. Issue 6 (November 2021) - Nunes, Mariana De Oliveira; Overman, David M.; Casey, Susan A.; Witt, Dawn R.; Schmidt, Christian W.; Griffin, Lindsay; Rigsby, Cynthia K.; Han, B. Kelly
Background: Patients with single ventricle (SV) congenital heart disease (CHD) undergo several interventions in the first years of life. Advanced diagnostics are required for interstage assessment of anatomy, but are associated with significant diagnostic risk. We sought to evaluate image quality, risk, and accuracy of cardiac computed tomography (CCT) for evaluation of anatomy prior to superior cavopulmonary connection (SCPC) compared to surgical findings across 2 institutions. Methods: A retrospective evaluation of image quality, risk, and accuracy of pre-SCPC CCT was performed at 2 institutions between January 1, 2010 and September 30, 2016. Results: CCT was performed in 90 SV CHD patients with a median age of 4.03 months (interquartile range [IQR] 3.36, 5.33) prior to SCPC. Image quality was optimal (84%) or good (16%) in all patients, without significant discrepancy compared to surgical findings. 7 patients (8%) required interventional cardiac catheterization subsequent to CCT and before surgical intervention. 49% of scans were performed without sedation, 43% of scans were performed with mild to moderate sedation, and 8% of scans were performed with general anesthesia. The median total procedural dose-length product (DLP) was 18 (IQR 14, 26) mGy*cm, estimating an age adjusted radiation dose of 1.4 millisievert (mSv). One minor (1%) adverse event was reported within 24 h of the CCT. Surgical complications were unrelated to the presurgical findings. Conclusions: CCT for pre-SCPC evaluation is safe, with excellent accuracy for anatomy at the time of surgical intervention across 2 institutions. In select patients, noninvasive evaluation with CCT may be indicated.